Spatial Analyses of Invasion Patterns of Chinese Tallow (Triadica sebifera) in a Wet Slash Pine (Pinus elliottii) Flatwood in the Coastal Plain of Mississippi, USA. Issue 5 (25th May 2018) - Fan, Zhaofei
Abstract: By analyzing stem map and age data of invasive tallow ( Triadica sebifera ) in a slash pine ( Pinus elliottii ) flatwood, we examined the invasion process of tallow at a local scale (stand) in the Grand Bay National Wildlife Refuge, Jackson County, Mississippi, USA. Spatially, tallow seedlings and saplings are mostly distributed in areas near the stand edge (< 20 m from the road) and underneath overstory slash pines. More tallow seedlings and saplings and tallow seeds were found around snags, particularly those in advanced decay classes, than around live trees. Thick and tall shrub layers inhibit tallow colonization and growth. The observed spatial and temporal invasion patterns of tallows suggest that the risk of tallow invasion may be greatly increased by both natural and anthropogenic disturbances that promote the foraging and nesting of tallow seed-eating birds and seed dispersal as well as create favorable site conditions for seed germination and seedling growth. Restoration of pine flatwoods and desired stand conditions such as reducing canopy openness, retaining snags, and restoring the grassy ground layer may further facilitate the invasion of tallow in areas already invaded by tallow or within the distance that tallow seeds can be dispersed by birds.